Nursing care for a patient with diabetic foot: an experience report of the supervised internship (Research, Society and Development, 2021)
Introduction: The diabetic foot is one of the main complications of diabetes mellitus (DM). This term is used to characterize the presence of lesions in the feet caused by peripheral neuropathy, peripheral vascular disease and deformities. Methodology: This is a descriptive and observational study, of the case study type. Held in a Hospital in Timon-MA, developed in the discipline of Supervised Curricular Internship II, by nursing students, in the period between August and December 2018. Experience report: The practice of nursing internship requires a sensitive view from students and professionals that accompany them. Carrying out as much care as possible, helps the student to leave the internship with experiences of the reality of the profession's daily life. With this in mind, the authors took advantage of assisted practice to care for a 63-year-old male patient diagnosed with Diabetes Mellitus (DM) 3 years ago. The same had been admitted from another hospital in the region for the treatment of diabetic foot, injury to the Right Lower Limb (MID) with a clean and dry occlusive dressing. Final considerations: The nursing activities described in this experience report are not restricted to the mentioned patient, but to all patients with diabetic foot who need assistance to treat the disease and its complications, and need individualized follow-up and care. quality.